A qualitative exploratory interview study on birth companion support actions for women during childbirth - Eva Wodeya Wanyenze; Josaphat K. Byamugisha; Nazarius Mboona Tumwesigye; Patience A. Muwanguzi; Gorrette K. Nalwadda (BMC, 2022)
Abstract Background The World Health Organization recommends that women are supported continuously throughout labor by a companion of their choice. And, that companions have clearly designated roles and responsibilities to ensure that their presence is beneficial to both the woman and her health care providers. Presently, there is lack of strong evidence regarding specific support actions in relation to women's needs of care. Thus, we aimed to explore birth companion support actions for women during childbirth. Methods This was an exploratory descriptive qualitative study conducted between August 2019 and December 2019; at a referral hospital in the Eastern part of Uganda. Ten women were purposively selected: those who were admitted in early labor, expecting a normal delivery, and had fulltime birth companion. Nonparticipant direct observation and in-depth interviews were used to collect data. Latent content analysis was used. Results Three themes were identified: "Support actions aiding a good childbirth experience", "Support actions hindering coping with labor", and "Women's needs and expectations of care". Support actions aiding a good experience described were; emotional presence, motivation, providing nourishments, messenger activities, body massage for pain relief, assisting in ambulation and coaching. Companion fearful behaviors and disrespectful care in form of unacknowledged needs and hostility from birth companions were reported to hinder coping. The women desired thoughtful communication, trust, for birth companions to anticipate their needs and recognize non perceptive phases of labor to allow them focus on themselves. Conclusion Birth companions from this study largely supported women emotionally, and attended to their physical needs. The greater part of support actions provided were esteemed by the women. Presence of birth companion will be of benefit when individual needs of women are put into consideration. Also, more guidance for birth companions is necessary to boost their role and mitigate shortcomings of their presence during childbirth.